Anatomopathological evaluation of young bulls (Bos taurus) testicles submitted to immunocastration Avaliação anatomopatológica de testículos de bovinos (Bos taurus) superprecoces submetidos a imunocastração - Withoeft J.A.* (2019)
© 2019 Universidade Federal do Rio Grande do Sul. All rights reserved.Background: Immunocastration is a less invasive and painless procedure compared to surgical castration, which causes greater stress to animals, especially when performed improperly. Immunocastration stimulates the production of antibodies against Gonadotropin-Releasing Hormone (GnRH), temporarily blocking the hormone production by the male gonads. Anatomopathological evaluation of animals submitted to immunocastration with the establishment of different degrees of testicular degeneration helps to evaluate the efficacy of the different dose ranges used for this procedure. Because of the scarcity of information about this procedure in young bulls, the study aimed to compare the immunocastrated and non-castrated animals. Materials, Methods & Results: Eighteen Angus-Limousin bulls were used from weaning (7±1 months) to slaughtering (15±1 months) with the establishment of two groups composed of nine non-castrated (NC) and nine immunocastrated (IC) animals. In the IC group, three doses of GnRH synthesis inhibitor vaccine (Bopriva®) were applied on days 0 (weaning), 87 and 223. At slaughter, scrotal circumference, weight (kg), width (cm), length (cm) and total size (width x length) of the testicles were obtained, then were routinely processed for histopathological analysis. Four degrees of testicular degeneration was established: grade 0 (no changes), grade 1 (mild), grade 2 (moderate) and grade 3 (severe). Statistical analysis was performed using Student’s t-test to compare the means of macroscopic variables. The scrotal circumference started to decrease in the IC animals on day 132, with a certain growth from day 194. There was a significant difference between the two groups for width (P = 0.001), length (P = 0.004), total size (P = 0.003) and scrotal circumference (P = 0.04). Testicles of the IC group tended to be lighter (P = 0.06). The final difference between the groups was 6.3 cm for scrotal perimeter, with respective averages of 27.44 cm and 33.77 cm for the IC and NC group, respectively. In the microscopic evaluation, NC animals obtained grade 0. In the IC animals, 33.33% (3/9) had degeneration grade 1 with slight basement membrane tortuosity and Sertoli cell atrophy, 33.33% (3/9) obtained grade 2 with moderate tortuosity and thickening of seminiferous tubules, Sertoli and Leydig cell atrophy, and absence of spermatogenesis and 33.33% (3/9) reached grade 3, with decreased seminiferous tubules and a severe and diffuse atrophy of Leydig and Sertoli cells and complete absence of spermatogenesis, with a 1:5 ratio in seminiferous tubule diameter between NC and IC grade 3 animals, respectively. Discussion: There was a significant difference in several testicular macroscopic aspects between the two groups, similar to values using eight months old field-bred animals, with a difference of 8.78 cm between groups, also with the use of three doses of Bopriva. The only macroscopic variable that showed just a tendency of difference between the groups was testicular weight, whereas, in a study with crossbred animals with nine months old, there was a difference of 152 g in testicular weight between groups. Histologically, in immunocastrated two-year-old Nelore cattle, 85% demonstrated a total absence of spermatogenesis and 15% had a partial reduction, suggesting functional recovery of Sertoli cells after the last vaccination booster or partial inhibition of spermatogenesis. In this study, 90-day dose intervals produced effective immunization during 105 days, which is the suggested period for the third dose. The anatomopathological analysis proved to be effective for the comparison between the groups and the degree of the promoted degeneration.